Effect of non-genetic factors on voluntary and involuntary culling in Holstein Friesian crossbred cattle - DASH, SHAKTI KANT; GUPTA, ASHOK KUMAR; SINGH, AVTAR; MOHANTY, TUSHAR KUMAR; UPADHYAY, ARPAN; GUPTA, RAVI KANT; M, MANOJ (The Indian Journal of Animal Sciences, 2016)
The present study focused on analysis of annual disposal pattern and identification of non-genetic factors affecting the incidence of culling in Holstein Friesian crossbred cattle. Data on disposal pattern of 1988 Karan Fries (Holstein Friesian crossbred) cows, spread over a period of 34 years (1978 to 2012), were utilized for the study. Culling was classified into 2 groups viz. voluntary (low milk production) and involuntary culling. Reasons of involuntary culling were categorized into locomotory problem (LP), poor health and weakness (PHW), teat and udder problem (TUP) and reproductive problem (RP). Logistic regression analysis was conducted to assess the effect of various non-genetic factors viz. number of normal lactations completed (NLC), calving type (CT), season of calving (SC) and period of calving (PC) on incidence of culling in various parities. The analysis of annual disposal pattern of the Karan Fries cows, revealed that the average annual replacement index, annual culling rate and annual disposal rate in the herd was 1.46, 24.40 and 29.80% per annum, respectively. Odd ratio estimates indicated that young calvers which did not complete atleast one normal lactation were 1.83 times more prone to culling because of PHW and were 0.95 and 0.33 times lesser prone to culling due to RP and LMP, respectively. Moreover, receiver operating characteristic (ROC) analysis indicated that the role of non-genetic factors in prediction of culling increased with parities and the logistic regression was efficient in predicting the incidence of parity wise culling, due to different involuntary causes, in Karan Fries cattle.